2013
DOI: 10.1002/j.1532-2149.2013.00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Complex regional pain syndrome type I of the knee: A systematic literature review

Abstract: In our Center for Pain Medicine, a group of patients reported to have symptoms possibly attributable to complex regional pain syndrome (CRPS) of only the knee(s). Therefore, this study aimed to investigate whether the literature reports on patients with CRPS type I in the knee(s) alone and, if so, to summarize the reported diagnostics, aetiology and treatment strategies of CRPS of the knee(s). Medline, Embase, Cochrane Library, PubMed and Web of Science were searched for articles focusing on a painful disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Within the group of 12 patients who all finished the trial period, the following causes of the knee CRPS were given: 7 patients had undergone (arthroscopic) surgery or an arthroscopy, 4 patients had a trauma of the knee (2 had a luxation of the patella and 2 patients had fallen on the specific knee), and 1 patient had a fracture of the tibia plateau. The surgical causes of CRPS confined to the knee are in line with one of our earlier reports concerning CRPS confined to the knee …”
supporting
confidence: 89%
See 1 more Smart Citation
“…Within the group of 12 patients who all finished the trial period, the following causes of the knee CRPS were given: 7 patients had undergone (arthroscopic) surgery or an arthroscopy, 4 patients had a trauma of the knee (2 had a luxation of the patella and 2 patients had fallen on the specific knee), and 1 patient had a fracture of the tibia plateau. The surgical causes of CRPS confined to the knee are in line with one of our earlier reports concerning CRPS confined to the knee …”
supporting
confidence: 89%
“…We totally agree with the statement of the authors of the letter to the editor that “the incidence of CRPS knee following trauma or otherwise is not well appreciated.” We would like to refer to our earlier published paper in which we concluded that the scientific literature does report cases of complex regional pain syndrome (CRPS) type I of only the knee(s). Our recommendation was to consider CRPS confined to the knee as a medical entity and therefore to include CRPS of only the knee(s) in future research on the etiological mechanisms of and optimal treatment for CRPS …”
mentioning
confidence: 99%
“…Recently, a systematic review was performed to find evidence for the diagnosis of CRPS of the knee. The authors concluded that this diagnosis has been described before and the best therapy is yet to be found .…”
Section: Introductionmentioning
confidence: 95%
“…Signal intensity alterations related to disuse hyperemia are challenging to differentiate from those caused by early infection and marrow infiltration and particularly difficult to differentiate from those due to complex regional pain syndrome, which results in similar hyperemia and osteopenia. Complex regional pain syndrome should be diagnosed on the basis of clinical criteria, as the imaging findings are nonspecific (49).…”
Section: Patellar Sleeve Avulsion Fracture-patellarmentioning
confidence: 99%